A simple role of coral-algal symbiosis in coral calcification based on multiple geochemical tracers. (15th August 2018) - Inoue, Mayuri; Nakamura, Takashi; Tanaka, Yasuaki; Suzuki, Atsushi; Yokoyama, Yusuke; Kawahata, Hodaka; Sakai, Kazuhiko; Gussone, Nikolaus
Abstract: Light-enhanced calcification of reef-building corals, which eventually create vast coral reefs, is well known and based on coral-algal symbiosis. Several controversial hypotheses have been proposed as possible mechanisms for connecting symbiont photosynthesis and coral calcification, including pH rise in the internal pool, role of organic matrix secretion, and enzyme activities. Here, based on the skeletal chemical and isotopic compositions of symbiotic and asymbiotic primary polyps of Acropora digitifera corals, we show a simple pH increase in the calcification medium as the predominant contribution of symbionts to calcification of host corals. We used the symbiotic and asymbiotic primary polyps reared for 10 days at four temperatures (27, 29, 31, and 33 °C), five salinities (34, 32, 30, 28, and 26), and four pCO2 levels (<300, 400, 800, and 1000 µatm). As a result of analyzing multiple geochemical tracers (U/Ca, Mg/Ca, Sr/Ca, δ 18 O, δ 13 C, and δ 44 Ca), a clear and systematic decrease in skeletal U/Ca ratio (used as a proxy for calcification fluid pH) was observed, indicating a higher pH of the fluid in symbiotic compared to asymbiotic polyps. In contrast, Mg/Ca ratios (used as a tentative proxy for organic matrix secretion) and δ 44 Ca (used as an indicator of Ca 2+ pathway to the fluid) did not differ between symbiotic and asymbiotic polyps. This suggests that organic matrix secretion related to coral calcification is controlled mainly by the coral host itself, and a transmembrane transport of Ca 2+ does not vary according to symbiosis relationship. Skeletal δ 18 O values of both symbiotic and asymbiotic polyps showed offsets between them with identical temperature dependence. Based on a newly proposed model, behavior of δ 18 O in the present study seems to reflect the rate of CO2 hydration in the calcifying fluid. Since CO2 hydration is promoted by enzyme carbonic anhydrase, the offset of δ 18 O values between symbiotic and asymbiotic polyps is attributed to the differences of enzyme activity, although the enzyme is functional even in the asymbiotic polyp. Symbiotic δ 13 C values in the temperature and salinity experiments were higher compared to those in the asymbiotic polyps due to photosynthesis, although photosynthetic δ 13 C signals in the pCO2 experiment were masked by the dominant δ 13 C gradient in dissolved inorganic carbon in seawater caused by 13 C-depletd CO2 gas addition in the higher pCO2 treatments. Sr/Ca ratios showed a negligible relationship according to variation of temperature, salinity, and pCO2, although it might be attributed to relatively large deviations of replicates of Sr/Ca ratios in the present study. Overall, only the U/Ca ratio showed a significant difference between symbiotic and asymbiotic polyps throughout all experiments, indicating that the critical effect on coral calcification caused by symbiotic algae is the increase of pH of the calcifying fluid by photosynthesis.